Triplatin, a platelet aggregation inhibitor from the salivary gland of the triatomine vector of Chagas disease, binds to TXA2 but does notinteract with glycoprotein PVI - Ma, Dongying; Assumpção, Teresa C. F.; Li, Yuan; Andersen, John F.; Ribeiro, José M.C.; Francischetti, Ivo M.B. (Thrombosis and Haemostasis, 2012)
Salivary glands from haematophagous animals express a notable diversity of negative modulators of platelet function. Triplatin is an inhibitor of collagen-induced platelet aggregation which has been described as an antagonist of glycoprotein VI (GPVI). Because triplatin displays sequence homology to members of the lipocalin family of proteins, we investigated whether triplatin mechanism of action could be explained by interaction with pro-haemostatic prostaglandins. Our results demonstrate that triplatin inhibits platelet aggregation induced by low doses of collagen, thromboxane A2 (TXA2) mimetic (U46619), and arachidonic acid (AA). On the other hand, it does not inhibit platelet aggregation by convulxin, PMA, or low-dose ADP. Isothermal titration calorimetry (ITC) revealed that triplatin binds AA, cTXA2, TXB2, U46619 or prostaglandin (PG)H2 mimetic (U51605). Consistent with its ligand specificity, triplatin induces relaxation of rat aorta contracted with U46619. Triplatin also interacts with PGF2a and PGJ2, but not with leukotrienes, AA or biogenic amines. Surface plasmon resonance experiments failed to demonstrate interaction of triplatin with GPVI; it also did to inhibit platelet adhesion to fibrillar or soluble collagen. Because triplatin displays sequence similarity to apolipoprotein D (ApoD) – a lipocalin associated with high-density lipoprotein, ApoD was tested as a putative TXA2-binding molecule. ITC failed to demonstrate binding of ApoD to all prostanoids described above, or to AA. Furthermore, ApoD was devoid of inhibitory properties towards platelets activation by AA, collagen, or U46619. In conclusion, triplatin mechanism of action has been elucidated without ambiguity as a novel TXA2- and PGF2α- binding protein. It conceivably blocks platelet aggregation and vasoconstriction, thus contributing to successful blood feeding at the vector-host interface.
Keywords: Snake venoms; protein function / activity; platelet physiology